China's Hainan Free Trade Port: Medical Laws and Policy Reform - Qi, Fei; Wu, Yuqi; Wang, Jing; Wang, Qi (Frontiers in Public Health, 2021)
In 2018, the government of China decided to develop Hainan Province as the country’s first free trade port operating within the country’s socialist system. A recent law granted Hainan a high degree of legislative autonomy, which the province has used to extend its autonomy and reform its medical laws and policies. For example, Hainan has formulated policies for more rapid and con-venient access of foreign medicine and sanitary equipment (MSE), allowed manufacturers to reg-ister MSE in China with real-world data (RWD), and provided legal and visa conveniences for international medical teams to carry out various activities, including: diagnosis, treatment and scientific research. Hainan's reforms are not only conducive to the improvement of local medical and public health levels, but also provide opportunities for international MSE manufacturers and medical research institutions swiftly to enter China’s huge medical market. However, with op-portunity comes risk: Hainan should be on guard against public health risks associated with medical tourism, and decide how to strike a reasonable balance between protecting local MSE enterprises and improving the accessibility of imported MSE through policies and legislation.